Development of a Convolutional Neural Network for Classification of Type of Vessels - Nascimento, Ariel Victor do; Rocha, Marcus Pinto da Costa da; Farias, Valcir João da Cunha; Neto, Miércio Cardoso de Alcântara (International Journal of Advanced Engineering Research and Science, 2023)
in this paper, was used a method which use concepts of intelligence artificial, machine learning, deep learning for Classification of Type of Vessels. With a technique from deep learning called Convolutional Neural Network (CNN) was applied to recognize images to identify the type of ship and to use the same method to identify if the vessel. The CNN projected with determined 5 layers, the first layer containing 32 neurons, the second layer with 64 neurons, the third layer with 128 neurons, the fourth layer with 512 neurons. Activation functions for these specified layers contain the ReLU function. The fifth and last layer is the output layer is the output layer, so the number of neurons is equal to the number of vessel type. In our study six classes were used, which are the vessel types, in this layer the activation function was the Softmax. The CNN generate satisfactory results, where could get results of prediction with all corrects answers to identify the ship.